A construção social dos riscos sócio-ambientais causados pelo processo produtivo convencional de cana-de-açúcar um estudo de sustentabilidade sócio-ambiental - Sousa, Iara Fonseca de (2010)
The reality could be perceived in different ways due mainly to the culture and social assumptions embody in each group, comunity or society. This work attempeted to compose a major frame of the social construction about the socio-environmental risks caused by the convecional product process of sugarcane, by using a perspectivy study of the Monte Alegre rural settlement productors. This perceptions were also related and contested by the tecnoscientific information available for the the impacts occasioned by the sugar-cane production to adress convergence or divergence contacts. The risk perception study is justified by the recognition of the important role played by the several social actors in the desenvelopment and management of their areas, within this, the essencial step for reaching a better sustentability of the rural environment. The metodology use quantitativity and qualitativity approaches by the application of close questtionares, semi-structured interviews and photodocumentation. It's important to notice that there are sensitive divergence and convergence between the productors percepcions and the tecno-scientific production, that reenforce the importance of the complementary and incoporation of different knowleges in the planning and execution plans of the study area management.